The association between psychosocial characteristics at work and problem drinking: a cross-sectional study of men in three Eastern European urban populations. Issue 8 (26th July 2005) - Bobak, M; Pikhart, H; Kubinova, R; Malyutina, S; Pajak, A; Sebakova, H; Topor-Madry, R; Nikitin, Y; Caan, W; Marmot, M
Abstract : Background: Psychosocial factors at work are thought to influence health partly through health behaviours. Aims: To examine the association between effort-reward imbalance and job control and several alcohol related measures in three eastern European populations. Methods: A cross-sectional study was conducted in Novosibirsk (Russia), Krakow (Poland), and Karvina (Czech Republic). The participants completed a questionnaire that included effort-reward at work, job control, and a number of sociodemographic variables. Annual alcohol intake, annual number of drinking sessions, the mean dose of alcohol per drinking session, and binge drinking (⩾80 g of ethanol in one session at least once a week) were based on graduated frequencies in the questionnaire. Data were also available on problem drinking (⩾2 positive answers on CAGE questionnaire) and negative social consequences of drinking. All male participants in full employment (n = 694) were included in the present analyses. Results: After controlling for age and centre, all indices of alcohol consumption and problem drinking were associated with the effort-reward ratio. Adjustment for material deprivation did not change the results but adjustment for depressive symptoms reduced the estimated effects. Job control was not associated with any of the alcohol related outcomes. Conclusions: The imbalance of effort-reward at work is associated with increased alcohol intake and problem drinking. The association appears to be partly mediated by depressive symptoms, which might be either an antecedent or a consequence of men's drinking behaviour.